Layanan Pos Bantuan Hukum (Posbakum) di Pengadilan Agama Kota Pangkalpinang Kelas 1A - Sobari, Alwan (ISLAMITSCH FAMILIERECHT JOURNAL, 2024)
The legal aid post is one of the units in the court to assist underprivileged people in obtaining information, consultation and legal advice as well as preparing legal document needed by underprivileged people. According to supreme court regulation no.1 of 2014 concerning guideline for providing legal service to underprivileged people in court, there are three scopes of providing legal service to underprivileged people, namely court case fee waiver service outside the court building and legal aid post in the general court environment, religious court, and state administrative court. Pangkalpinang religious court is the one that has implemented this service. However, from observation and research carried out by the research team, the provision of free legal aid service is considered to be less targeted because it was found that there were people who received them in the “well-off “ category, so that many people who are truly poor cannot get free legal aid. This is only because the quota is limited and has been used for previous cases. Therefore, ,according to the research team, an evaluation is needed by the Pangkalpinang religious court to really find out the real domicile of the people who apply for this legal aid post service so that it can be assessed and decided whether they are worthy or not to receive the legal aid service. So, it is hoped that the state budget for legal aid service will be truly targeted and given to underprivileged people in obtaining legal aid service.